Una comparación entre los mitos de la creación del Suwá y del Timeo de Platón - Borrasé Fernández, Rocío (Revista de Filosofía de la Universidad de Costa Rica, 2014)
The principal goal of this paper is to compare the bribri creation myth and Plato’s myth of creation according to Timaeus, or about Nature, in order to evince how the holistic world vision of bribri people and an anthropocentric world vision world like Plato’s can carry to the establishment of qualitatively different connections between human species and other species existing in the world.